Negotiating postcolonial legacies: shifting conservation narratives and residual colonial built heritage in Ireland. Issue 2 (13th March 2015) - Parkinson, Arthur; Scott, Mark; Redmond, Declan
Abstract : Where they evolve in contentious political contexts, conservation and heritage can be framed by competing priorities reflecting collective remembering, cultural politics and identities intertwined with the symbolic representation of the built environment. Drawing on postcolonial experiences in Ireland, this paper explores the shifting representations of built heritage over the post-independence era and the extent that a residual colonial legacy can perform a role in framing contemporary place-making processes. Empirically, we focus on representations emerging within contemporary 'elite discourses' - built heritage policy-makers, leading conservation practitioners and civil society conservation groups - to explore how they negotiate this postcolonial context. The research on which this article is based was partly funded by the Irish Research Council through the Graduate Research Education Programme.